De-Professionalization of Cataloging and Classification Practitioners in the Digital Environment: Retooling and Reskilling Issues in Academic Libraries in Nigeria. Issue 6 (18th August 2019) - Olayemi, Kemi Jummai; Olayemi, Olalekan Moses
Abstract: This article discusses issues of de-professionalization that is fast eroding cataloging and classification practices in academic libraries in Nigeria. It focuses on the factors that led to de-professionalization, its effect on cataloging and classification practices, and the need to re-strategize by retooling and reskilling the cataloging librarian in order to continue to remain relevant in the digital environment.